Examining Conceptual Understanding and Engagement in Mathematics Students - P. Balacuit, Ian Cesar; B. Nabua, Edna; G. Saludares, James Rey (Indonesian Journal of Mathematics Education, 2025)
This study examines the relationship between conceptual understanding and the level of engagement students in mathematics. Conceptual understanding was assessed across key mathematical topics, including sequences, polynomials, circles, coordinate geometry, combinatorics, probability, and measures of position. On the other hand, engagement was assessed through its cognitive, behavioral, emotional, and social dimensions. Employing a descriptive-correlational research design, this study considered data from 128 students selected through proportional sampling. A researcher-made test was used to measure conceptual understanding, and a validated scale was adopted to assess student engagement. Descriptive statistics showed that 39.4% of students had very low conceptual understanding, while only 8.59% demonstrated a very high level. The students have very low performance in topics such as factoring polynomials and interpreting measures of position. Engagement levels varied, with students reporting the lowest level of engagement in terms of cognitive dimension (x̄ = 2.59), while behavioral (x̄ = 2.80), emotional (x̄ = 2.90), and social engagement (x̄ = 2.89) were at moderate levels. This study found significant positive correlations between conceptual understanding and all dimensions of engagement, with the strongest relationship observed between conceptual understanding and social engagement (p = 0.629, p = 0.001). These findings highlight the consistent association between engagement and learning outcomes. This study suggests that future research be initiated to improve student engagement and conceptual understanding in mathematics.